Differential expression of sex regulatory genes in gonads of Astyanax mexicanus surface fish and cavefish - Kaitlyn A. Webster; Bethany Ponte; Hans Vasquez-Gross; Juli Petereit; John Hutchinson; Misty R. Riddle (BMC Ecology and Evolution)
Abstract Background Astyanax mexicanus is a single species of fish that consists of river-dwelling (surface) and cave-dwelling morphotypes. Little is known about how sexual determination, differentiation or reproduction have evolved in the surface morphs or cavefish, though divergence in reproductive strategy is expected as the latter have adapted to the novel cave environment. Evolution of the gonad transcriptome may underlie the differences in gamete morphology, fertility, and fecundity previously reported between morphotypes. Results We compared the ovary and testis transcriptome of surface fish and cavefish at juvenile and adult stages. We found that samples clustered by developmental stage, sex, and morphotype identity. Several key genes that are typically associated with the female gonad in other vertebrates showed a reversal in sexual dimorphism or were not differentially expressed between sexes in A. mexicanus. In contrast, gene expression typically associated with male gonads was largely conserved and consistent with vertebrate testicular expression profiles. Transcriptional and physiological differences between surface fish and cavefish morphotypes were observed in gonads from both sexes. Cavefish ovaries exhibited unique upregulation of neuron development and differentiation genes, and extensive innervation of the ovarian epithelium, while cavefish testes showed increased expression of angiogenesis regulating genes, and greater vasculature density compared to surface fish testes. Conclusions These results reveal significant gene expression differences between A. mexicanus surface fish and cavefish morphotypes that may have functional consequences in gonad morphogenesis and fertility. Our findings provide a foundation for investigating the evolution of sex regulatory pathways and reproductive strategies in animals adapting to new and challenging environments in which nutrient availability, temperature, and mate selection are suboptimal.